2022
DOI: 10.1007/s10518-021-01303-w
|View full text |Cite
|
Sign up to set email alerts
|

Calculating earthquake damage building by building: the case of the city of Cologne, Germany

Abstract: The creation of building exposure models for seismic risk assessment is frequently challenging due to the lack of availability of detailed information on building structures. Different strategies have been developed in recent years to overcome this, including the use of census data, remote sensing imagery and volunteered graphic information (VGI). This paper presents the development of a building-by-building exposure model based exclusively on openly available datasets, including both VGI and census statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The availability of building-by-building data allows for a punctual definition of both seismic input and damage, avoiding the uncertainty driven by aggregated models (e.g. Nievas et al 2022). The PBS scenario in terms of PGA is combined with the fragility model resulting from the hybrid strategy (PBS + ShakeMap).…”
Section: Validation Against Observed Damagementioning
confidence: 99%
“…The availability of building-by-building data allows for a punctual definition of both seismic input and damage, avoiding the uncertainty driven by aggregated models (e.g. Nievas et al 2022). The PBS scenario in terms of PGA is combined with the fragility model resulting from the hybrid strategy (PBS + ShakeMap).…”
Section: Validation Against Observed Damagementioning
confidence: 99%
“…Although this type of volunteer-acquired data lacks standardised formats and completeness [40,41], the data offer valuable information on the spatial location of certain attributes without necessarily performing time-consuming in situ data collection. They have proved useful for acquiring socio-economic indicators [42]), assessing the physical vulnerability of local buildings to earthquakes (e.g., [43][44][45]) and floods (e.g., [46,47]), and in global exposure initiatives [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…However, such time-demanding and cost-intensive approaches are decreasingly able to cope with the high spatiotemporal dynamics of built environments. Simultaneously, the information provided on a coarser spatial level, such as spatially aggregated census data (e.g., Corbane et al 2017;Santa Maria et al 2017;Yepes-Estrada et al 2017), hampers the consideration of small-scale hazard effects in a downstream risk model (Gomez Zapata et al 2021;Nievas et al 2022) and frequently shows a high level of uncertainty (Pittore et al 2017). Moreover, recent empirical works underlined that the accuracy of damage estimates is very sensitive regarding the exposure component (Gomez-Zapata et al 2022a, b), whereby the coarsest aggregation levels were found to be the most inaccurate (Senouci 2018;Dabbeek et al 2021).…”
Section: Introductionmentioning
confidence: 99%